Preparation of hexamethylol melamine resin with low crystallization water and low viscosity for hexamethylol melamine/polyvinyl alcohol composite membrane - Liu Xing-Jian; Guo Yan-Wen; Zheng Jian-Fei; Wu Jiang; Hu Bing (Polish Journal of Chemical Technology, 2022)
Hexamethylol melamine resins (HMM) with low crystallization water content and low viscosity were prepared by inhibiting the condensation polymerization of low hexamethylol melamine. The effects of catalyst, pH, formalde-hyde/melamine ratio, reaction temperature and time on the synthesis parameters of HMM were investigated. The results showed that the sample (HMM8) synthesized with Na2CO3-NaHCO3 as catalyst had the crystallization water content lower than 10%, being with a viscosity of about 0.26 Pa·s. The melting temperature of HMM8/polyvinyl alcohol (PVA) curing system was about 164.3 °C. It was found that the higher the amount of formaldehyde, the greater the hydroxyl methyl bounded to each triazine ring. Compared with the traditional melamine formaldehyde resin which had the crystallization water content of about 20–30%, the production of this resin was expected to reduce the energy consumption of industrial reaction, while the resin with 10% crystallization water content was more conducive to the development of alloying HMM/PVA composite membrane.